STRATEGI BRAND DESTINATION PASAR KUMANDANG SEBAGAI UPAYA PEMBENTUKAN DIGITAL DESTINATION DI KABUPATEN WONOSOBO - Bramantia Putra, Ibrahim; ., Chusmeru; Widodo, Bambang (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p02, 2020)
This study aims to know the role or strategy of brand destination used by Pasar Kumandang in forming a digital destination in Wonosobo to try to increase the number of visits, and to know the supporting and inhibiting factors in the management of Pasar Kumandang. The method used in this study is a qualitative descriptive technique with the selection of informants by purposive sampling. In collecting data, this study uses interviews, observation and documentation. Existing data were analyzed using the SWOT analysis model and 4A Components (Attraction, Accessibility, Amenity, and Ancillary). Broadly speaking, the results of this study indicate that there are several strategies that can be used in Pasar Kumandang, namely by optimizing attractiveness or tourism activities, maximizing all forms of tourism activities, and coordinating better with various parties. As well as maximizing promotional activities, which aim to provide a positive assessment. This study has found supporting factors in the management of Pasar Kumandang, which is supported by the enthusiasm of the surrounding community, having adequate facilities to meet the needs of visitors, and the concept of being cultured and environment-based. The inhibiting factors are lack of funds to renew some outdated facilities, lack of attention from the local government, and lack of human resources.